A biological staging model for operable non-small cell lung cancer. Issue 7 (1st July 2001) - Cox, G; Jones, J L; Andi, A; Waller, D A; O'Byrne, K J
Abstract : BACKGROUND: Currently the best prognostic index for operable non-small cell lung cancer (NSCLC) is the TNM staging system. Molecular biology holds the promise of predicting outcome for the individual patient and identifying novel therapeutic targets. Angiogenesis, matrix metalloproteinases (MMP)-2 and -9, and the erb/HER type I tyrosine kinase receptors are all implicated in the pathogenesis of NSCLC. METHODS: A retrospective analysis of 167 patients with resected stage I–IIIa NSCLC and >60 days postoperative survival with a minimum follow up of 2 years was undertaken. Immunohistochemical analysis was performed on paraffin embedded sections for the microvessel marker CD34, MMP-2 and MMP-9, EGFR, and c-erbB-2 to evaluate the relationships between and impact on survival of these molecular markers. RESULTS: Tumour cell MMP-9 (HR 1.91 (1.23–2.97)), a high microvessel count (HR 1.97 (1.28–3.03)), and stage (stage II HR 1.44 (0.87–2.40), stage IIIa HR 2.21 (1.31–3.74)) were independent prognostic factors. Patients with a high microvessel count and tumour cell MMP-9 expression had a worse outcome than cases with only one (HR 1.68 (1.04–2.73)) or neither (HR 4.43 (2.29–8.57)) of these markers. EGFR expression correlated with tumour cell MMP-9 expression (p<0.001). Immunoreactivity for both of these factors within the same tumour was associated with a poor prognosis (HR 2.22 (1.45–3.41)). CONCLUSION: Angiogenesis, EGFR, and MMP-9 expression provide prognostic information independent of TNM stage, allowing a more accurate outcome prediction for the individual patient. The development of novel anti-angiogenic agents, EGFR targeted therapies, and MMP inhibitors suggests that target specific adjuvant treatments may become a therapeutic option in patients with resected NSCLC.